Molecular biology and biotechnology of plant organelles : (Springer, 2004)
This book details not only basic concepts &​ current understanding of plant organelle genetics and molecular biology but also focuses on the synergy between basic biology and biotechnology. Forty-four authors from nine countries have contributed twenty-four chapters containing many figures and tables.